2018
DOI: 10.1093/infdis/jiy433
|View full text |Cite
|
Sign up to set email alerts
|

The Induction of IL-1β Secretion Through the NLRP3 Inflammasome During Ebola Virus Infection

Abstract: The inflammasome is part of the innate immune system that regulates the secretion of proinflammatory cytokines such as interleukin-1β (IL-1β). Ebola virus (EBOV) infection of monocytes and macrophages (primary target cells early during infection) leads to the production of proinflammatory cytokines; however, the mechanism behind the activation and release of these cytokines is not fully understood. Here, we demonstrate that EBOV infection leads to the activation of the NLRP3 inflammasome and the subsequent sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…This inflammatory response was accompanied by an equally rapid and potent IL-10 response and somewhat lower levels of IL-12, IL-18, and IFN-α2. These data -in a highly relevant ex vivo system -corroborate previous observations from human cell lines and in vitro-generated monocyte-derived DCs and macrophages (11,14,16,18). The relatively low levels of NK cell-and T cell-activating cytokines together with the abundance of IL-10 suggest the generation of a tightly regulated cytokine environment within hours of exposure Figure 5.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This inflammatory response was accompanied by an equally rapid and potent IL-10 response and somewhat lower levels of IL-12, IL-18, and IFN-α2. These data -in a highly relevant ex vivo system -corroborate previous observations from human cell lines and in vitro-generated monocyte-derived DCs and macrophages (11,14,16,18). The relatively low levels of NK cell-and T cell-activating cytokines together with the abundance of IL-10 suggest the generation of a tightly regulated cytokine environment within hours of exposure Figure 5.…”
Section: Discussionsupporting
confidence: 86%
“…Impairment of the type I IFN response is accompanied by an excessive proinflammatory cytokine response (2,13). In vitro studies have shown that the Ebola virus GP is a potent ligand for TLR-4 and induces activation of noninfected monocytic cell lines and monocyte-derived DCs and macrophages to produce cytokines (14)(15)(16)(17)(18). Importantly, an initial type I IFN response accompanied by modest and transient IL-1β and TNF-α secretion correlated with survival among EVD patients, whereas high IL-10 was associated with fatal outcome (13,19,20).…”
Section: Resultsmentioning
confidence: 99%
“…NLRP3 is an innate immune signaling receptor. Once activated, it initiates caspase1-mediated proteolytic activation of the IL-1β family of cytokines, and induces an inflammatory response [23][24][25]. The expression of these innate immune Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also show that NLRP3 is also a sensor for viral infection. NLRP3 inflammasome signalling drives IL‐1β production in Ebola infection 84 . However, some viruses, such as Sendai virus and NS1 mutant influenza A virus, inhibit IL‐1β production by preventing NLRP3 assembly and detection of these viruses, highlighting the limitations of NLRP3 in combating such viral infections 85,86 .…”
Section: Inflammasomes: Key Mediators Of Inflammatory Diseasesmentioning
confidence: 99%